Implementation of the Flipped Classroom Learning Model to Improve Students' Language Skills at MI Miftahul Jannah - Sa’diyah, Jamilatus; Soliha, Imro Atus (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study examined the effectiveness of the flipped classroom model in improving language proficiency among 20 fourth-grade elementary students at MI Miftahul Jannah, Kedung Supit. The flipped classroom approach allows students to independently review materials before class, maximizing in-class time for interactive and collaborative learning. Employing a qualitative research design with experimental pre-test/post-test components and descriptive methods, data were collected via observations and interviews. Analysis involved data reduction, presentation, and conclusion drawing. Language proficiency assessments and motivation questionnaires served as instruments. Results showed the flipped classroom significantly enhanced students' language abilities, particularly in speaking and writing, and fostered greater enthusiasm and engagement. The model’s implementation involved three phases: pre-class material review using worksheets; in-class discussions and exercises guided by the teacher; and post-class formative assessments. A notable improvement in listening and speaking skills was observed. Previously, students struggled with main ideas, new vocabulary, and expressing opinions due to time and improper language use. After adopting the flipped classroom, 15 of 20 students demonstrated significant progress, outperforming traditional methods. Furthermore, motivation questionnaires indicated increased student drive. This research confirms the flipped classroom as an effective strategy for boosting elementary language proficiency and offers a valuable resource for innovative teaching practices.